Risk of anterior cruciate ligament injury in population with elevated body mass index - Hasan N. Alsayed; Mohammed Abdulrahman Alkhateeb; Asma Abdulaziz Aldossary; Khalid Mohsen Houbani; Yousef Mohammed Aljamaan; Yousef A. Alrashidi (Medicinski glasnik, 2022)
Aim: Anterior cruciate ligament (ACL) injury is among the most common orthopaedic injuries. The elevated body mass index (BMI) can contribute to non-contact ACL injury. This study aims to assess the risk of ACL injury among elevated BMI population people (BMI ?25 Kg\m2). Methods: This is a cross sectional study that was conducted in a tertiary care centre in the Kingdom of Saudi Arabia. A total of 302 patients, who had an ACL reconstruction surgery in a ten-year-period (January 2008 to December 2018) were included. Results: Sport related injury is significantly higher among the overweight and obese groups (p=0.002). Moreover, the combined ACL tear was higher among the overweight and obese groups (p=0.001). In univariate regression analysis for the selected baseline characteristics, it was found that individuals with higher BMI have chance to develop combined (ACL) injury 2 times higher when compared to those with isolated ACL injury (p=0.003). Also, the ACL type, mode of injury, types of injury and type of sports were statistically significant in univariate regression analysis. However, only the mode of injury was statistically significant after controlling the confounding factors. Other selected variables like type of sport, type of injury and ACL type were not significant. Conclusion: Elevated BMI was associated with a higher risk of developing combined ACL tear as well as reinjured individuals.
Keywords: anterior cruciate ligament reconstruction; BMI; knee injury; obesity; sport injury